The effect of effective teaching strategy according to the method of resolving problems in the development of creative thinking and the level of skilled performance in futsal championships - Mohammed Nuhad, Tariq (International Journal of Psychosocial Rehabilitation, 2020)
The emergence of the impact of active learning strategy according to the method of self-revision in learns some football skills and maintained by the positive results of the tests in question Testing results showed tribalism and 117 sets of empirical research (code) the emergence of moral differences for the benefit of the results of the tests - 37484536 learn some skills of football The largest proportion of appeared to the Pilot Group of the retention of the officer group due to the use of the proposed educational program active learning strategy according to the method of self-revision in the education of some of the skills of football New educational programs for active learning strategy are used of in a manner of self-revision in the teaching football skills and other sporting skills He urged teachers to prepare programs of educational models make the student to an active element in the lesson and has the right to take decisions, responsible for its implementation Further studies on the impact of the educational program under discussion to ensure its effectiveness in learning different sports events and skills, whether individual or collective.